Effect of essential oils and major compound on Clostridium botulinum endospores inoculated in meat product (Research, Society and Development, 2022)
Mortadella is a widely consumed product due to its sensory characteristics, however, nitrite is used as a preservative and this synthetic additive has been linked to some diseases. In this sense, this study aimed to evaluate the antimicrobial effect of oregano and clove essential oils, besides the major compound carvacrol on Clostridium botulinum endospores inoculated in mortadella and the physicochemical effect of them on the product. The minimum sporicidal concentration of the essential oils and the major compound was determined by the broth microdilution method and the best results used to prepare the mortadellas containing 0 and 150 ppm of nitrite. All the evaluated treatments showed decrease of nitrite levels over time and lower lipid oxidation. The combinations of essential oils and carvacrol did not affect the mortadella color in the final product. In the mortadellas added of combinations of essential oils and of major compound there was reduction in the population of C. botulinum, whereas in mortadella without essential oils the antimicrobial effect was attributed only to the nitrite. The results are promising and suggest the use of clove and oregano essential oils together with carvacrol compound in meat sausages as a natural preservative and action against foodborne pathogens.